A COMPARATIVE STUDY ON HEALTHY AND CLEAN LIFESTYLE (PHBS) IN ELEMENTARY SCHOOL BASED ON GEOGRAPHICAL LOCATION - Yudha Febrianta; Sriyanto Sriyanto; Pratik Hari Yuwno (Universitas Muhammadiyah Purwokerto, 2021)
Theoretically this research was based on that health which affect cleanliness appriciate behavior. This research aiming to find out the difference of healthy and clean lifestyle for elemantary school student based on geographical location between highland and lowland. Proportionate stratified random sampling was used to decide the sample. Questionnaire was used toward 184 respondent to collect the data. Independent t- test with assist from SPSS V 23. 0 Software were used to analized collected data. The result of this research are ; there is a significant differences of healthy and clean lifestyle pattern between elementary school in sub-district baturraden banyumas with sub-distcrict petanahan Kebumen. The conclusion from the research is , student from highland applied more clean lifestyle pattern than lowland student.